Nitrogen, sulfur doped nanocarbon material, preparation method thereof, capacitor electrode material, capacitor electrode and preparation method thereof, and capacitor
Patent Information
- Application Number
- CN202110956876.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-19
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-08-19
AI Technical Summary
[0007]本发明的目的是为了克服现有技术存在的碳材料的比容量、倍率性能和循环性能不佳的问题,提供一种氮、硫掺杂纳米碳材料及其制备方法、电容器电极材料、电容器电极及其制备方法和电容器,以实现碳材料的比容量、倍率性能和循环性能的提升
[0018] (1) The nitrogen- and sulfur-doped carbon nanomaterials provided by this invention have microporous and mesoporous structures, and a BET specific surface area of 800-2000 m². 2 /g, the proportion of the specific surface area within the micropores to the total specific surface area is 50-85%; the total pore volume is greater than 1cm³. 3The micropore volume accounts for 30-50% of the total pore volume. X-ray photoelectron spectroscopy analysis shows that the carbon content on the surface of this nanomaterial is 70-95% by mass, nitrogen is 3-20% by mass, and sulfur is 0.1-10% by mass. Elemental analysis shows that the carbon content in this nanomaterial is 30-60% by mass, nitrogen is 1-15% by mass, and sulfur is 1-15% by mass. This nanomaterial possesses a multi-level porous structure dominated by micropores, abundant three-dimensional transport channels, and a large specific surface area. Nitrogen and sulfur atoms in the nanomaterial work synergistically, and through physical adsorption and ion intercalation, it effectively enhances the lithium storage performance of the material.
Smart Images

Figure CN115708180B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage technology, specifically to nitrogen and sulfur doped nano-carbon materials and their preparation methods, capacitor electrode materials, capacitor electrodes and their preparation methods, and capacitors. Background Technology
[0002] With the depletion of fossil fuels and the intensification of environmental problems, new energy sources have become a global focus to ensure sustainable development. Thanks to the deepening of energy utilization, energy storage devices such as lithium-ion batteries and supercapacitors have made significant progress in recent years. However, with the expansion of the electric vehicle market, higher demands are being placed on the energy density and power density of energy storage devices. While traditional lithium-ion batteries have high energy density, their low power density cannot meet high-power output requirements. Supercapacitors are a new type of green energy storage device that falls between traditional capacitors and batteries, featuring short charging time, long lifespan, good temperature characteristics, energy saving, and environmental friendliness. Compared to lithium-ion batteries, supercapacitors have higher power density and cycle stability. Electrode materials are a key factor in improving the performance of supercapacitors. Currently, commonly used electrode materials include carbon materials, transition metal oxides, hydroxides, and conductive polymers. Among them, carbon materials mainly achieve energy storage by adsorbing electrolyte ions through their porous structure. Double-layer supercapacitors composed of carbon materials exhibit good charge-discharge capabilities and excellent cycle stability. Currently, porous activated carbon synthesized from raw materials such as biomass is the most widely used material in double-layer supercapacitors. Porous activated carbon possesses a high specific surface area and a large number of micropores, exhibiting excellent specific capacitance. Although activated carbon is abundant and inexpensive, its large specific surface area often leads to lower volumetric energy density in supercapacitors, while consuming more electrolyte.
[0003] While supercapacitors possess very high power density and cycle stability, their low energy density fails to meet requirements. Lithium-ion capacitors, as a combination of lithium-ion batteries and supercapacitors, effectively compensate for the shortcomings of both. Lithium-ion capacitors consist of the positive electrode material of an electric double-layer capacitor and the negative electrode material of a lithium-ion battery, enabling them to achieve both high power density and high energy density. Currently, graphite materials, including natural and artificial graphite, are the most commonly used negative electrodes in lithium-ion capacitors. Although graphite materials are widely used in lithium-ion batteries, their rate performance is low, creating a kinetic matching problem with the positive electrode material in lithium-ion capacitors. Therefore, developing novel carbon negative electrode materials to further improve capacity, rate performance, and cycle life is a crucial means to solve the positive and negative electrode matching problem in lithium-ion capacitors.
[0004] To address the numerous shortcomings of electrode materials in double-layer supercapacitors and lithium-ion capacitors, various porous carbon materials have been developed, including graphene, carbon nanotubes, templated carbon, and carbon nanocages. Thanks to their regular shape, tunable pore structure, and excellent conductivity, carbon nanocages show promising application prospects in energy storage. Synthesis methods for carbon nanocages include activation methods, template methods, hydrothermal methods, high-temperature pyrolysis methods, chemical vapor deposition, and carbonization-gel methods.
[0005] Furthermore, doping with heteroatoms such as nitrogen and sulfur can effectively improve the conductivity and wettability of carbon materials, and can also introduce pseudocapacitance through redox reactions, thereby increasing the overall capacitance. There are two main methods for heteroatom doping. One is a post-processing method, which involves activating the carbon material at high temperature in a heteroatom-containing gas or heating it with heteroatom-containing organic compounds. The other method uses heteroatom-containing polymers as raw materials, retaining some heteroatoms during the carbonization process. Currently reported heteroatom doping mainly focuses on single-atom doping; multi-atom doping suffers from problems such as complex processes and high costs.
[0006] Nitrogen and sulfur doping is of great significance for improving the electrochemical performance of nano-carbon cages. However, achieving doping with multiple elements simultaneously while ensuring a regular material structure with abundant pores and a high specific surface area presents certain challenges. Summary of the Invention
[0007] The purpose of this invention is to overcome the problems of poor specific capacity, rate performance and cycle performance of carbon materials in the prior art, and to provide a nitrogen and sulfur doped nano-carbon material and its preparation method, a capacitor electrode material, a capacitor electrode and its preparation method and a capacitor, so as to improve the specific capacity, rate performance and cycle performance of carbon materials.
[0008] To achieve the above objectives, the first aspect of the present invention provides a nitrogen- and sulfur-doped carbon nanomaterial, wherein the carbon nanomaterial has a microporous structure and a mesoporous structure, and the BET specific surface area of the carbon nanomaterial is 800-2000 m². 2 / g, the proportion of the specific surface area within the micropores to the total specific surface area is 50-85%; the total pore volume of the nano-carbon material is greater than 1 cm³. 3 / g, the proportion of micropore volume to total pore volume is 30-50%; the mass percentage of carbon on the surface of the nano-carbon material, as determined by X-ray photoelectron spectroscopy, is 70-95%; the mass percentage of nitrogen is 3-20%; the mass percentage of sulfur is 0.1-10%; the mass percentage of carbon in the nano-carbon material, as determined by elemental analysis, is 30-60%; the mass percentage of nitrogen is 1-15%; the mass percentage of sulfur is 1-15%.
[0009] A second aspect of this invention provides a method for preparing nitrogen- and sulfur-doped carbon nanomaterials, the method comprising the following steps:
[0010] (1) Precursor preparation: A homogeneous solution is formed by mixing a nickel salt, a nitrogen-containing organic acid and a sulfur-containing potassium salt with a solvent, and then the solvent in the homogeneous solution is removed to obtain the precursor. The nitrogen-containing organic acid is ethylenediaminetetraacetic acid and / or 2,5-pyridinedicarboxylic acid, and the sulfur-containing potassium salt is potassium sulfate and / or potassium hydrogen sulfate.
[0011] (2) Calcination: Under an inert atmosphere, the precursor obtained in step (1) is calcined to obtain the pyrolysis product;
[0012] (3) Acid washing: Provide an aqueous solution containing the pyrolysis product obtained in step (2) and react it with acid, then separate the solid and liquid, wash and dry.
[0013] A third aspect of the present invention provides a capacitor electrode material comprising an active substance, a conductive agent, and a binder, wherein the active substance is the nitrogen- or sulfur-doped nanocarbon material described in the first aspect or the nitrogen- or sulfur-doped nanocarbon material prepared according to the preparation method described in the second aspect.
[0014] A fourth aspect of the present invention provides a capacitor electrode, the electrode comprising a current collector and an electrode material coated and / or filled on the current collector, wherein the electrode material is the electrode material described in the third aspect.
[0015] The fifth aspect of the present invention provides a method for preparing a capacitor electrode, the method comprising coating and / or filling a slurry containing an active material, a conductive agent, a binder, and a solvent onto a current collector, drying, and calendering or not calendering, wherein the active material is the nitrogen- or sulfur-doped nano-carbon material described in the first aspect or the nitrogen- or sulfur-doped nano-carbon material prepared according to the preparation method described in the second aspect.
[0016] The sixth aspect of the present invention provides a capacitor comprising a button-type housing, electrodes, a separator, and an electrolyte, wherein the electrodes comprise the capacitor electrodes described in the fourth aspect or capacitor electrodes prepared according to the preparation method described in the fifth aspect.
[0017] Through the above technical solution, the present invention has the following advantages:
[0018] (1) The nitrogen- and sulfur-doped carbon nanomaterials provided by this invention have microporous and mesoporous structures, and a BET specific surface area of 800-2000 m². 2 / g, the proportion of the specific surface area within the micropores to the total specific surface area is 50-85%; the total pore volume is greater than 1cm³. 3The micropore volume accounts for 30-50% of the total pore volume. X-ray photoelectron spectroscopy analysis shows that the carbon content on the surface of this nanomaterial is 70-95% by mass, nitrogen is 3-20% by mass, and sulfur is 0.1-10% by mass. Elemental analysis shows that the carbon content in this nanomaterial is 30-60% by mass, nitrogen is 1-15% by mass, and sulfur is 1-15% by mass. This nanomaterial possesses a multi-level porous structure dominated by micropores, abundant three-dimensional transport channels, and a large specific surface area. Nitrogen and sulfur atoms in the nanomaterial work synergistically, and through physical adsorption and ion intercalation, it effectively enhances the lithium storage performance of the material.
[0019] (2) The method for preparing nitrogen and sulfur doped nano-carbon materials provided by the present invention directly adds nitrogen and sulfur sources during the preparation of precursors. In the process of forming nano-carbon materials with a mixed morphology of hollow cage and sheet, nitrogen and sulfur doping and pore-forming activation are realized at the same time, which effectively improves the specific surface area of nano-carbon materials. The process is simple and easy to produce.
[0020] (3) When the nitrogen and sulfur doped nano-carbon material provided by the present invention is used as the negative electrode of a lithium-ion capacitor, the specific capacity after stabilization exceeds 800 mAh / g at a current density of 0.1 A / g; when the current density is increased to 2 A / g, the specific capacity can reach up to 300 mAh / g; at a current density of 1 A / g, after 1000 cycles, the capacity retention rate can reach up to 80%, showing excellent specific capacity, rate performance and cycle performance; as the electrode of a double-layer supercapacitor, when using an aqueous electrolyte, the single electrode specific capacitance can reach up to 358 F / g at a current density of 0.5 A / g, showing excellent capacitance performance. Attached Figure Description
[0021] Figure 1 This is a transmission electron microscope image of the nitrogen- and sulfur-doped carbon nanomaterials prepared in Example 1;
[0022] Figure 2 This is a high-resolution transmission electron microscope image of the nitrogen- and sulfur-doped carbon nanomaterials prepared in Example 1;
[0023] Figure 3 This is the N2 adsorption-desorption isotherm of the nitrogen and sulfur doped nanocarbon nanomaterials prepared in Example 1;
[0024] Figure 4 This is a complete scanning XPS image of the nitrogen- and sulfur-doped carbon nanomaterials prepared in Example 1;
[0025] Figure 5 The image shows the high-resolution S2p XPS spectrum of the nitrogen- and sulfur-doped carbon nanomaterials prepared in Example 1.
[0026] Figure 6 The image shows the Raman spectrum of the nitrogen- and sulfur-doped carbon nanomaterials prepared in Example 1.
[0027] Figure 7 The cyclic voltammetry curves of the nitrogen- and sulfur-doped carbon nanomaterials prepared in Example 1 at different scan rates are shown.
[0028] Figure 8 The constant current charge-discharge curves of the nitrogen- and sulfur-doped carbon nanomaterials prepared in Example 1 are shown.
[0029] Figure 9 This is a graph showing the capacitance and coulombic efficiency of the capacitor electrode prepared in Example B1 at different current densities;
[0030] Figure 10 This is a graph showing the capacitance and coulombic efficiency of the capacitor electrode prepared in Example B2 at different current densities;
[0031] Figure 11 This is a graph showing the capacitance and coulombic efficiency of the capacitor electrode prepared in Example B3 at different current densities;
[0032] Figure 12 This is a graph showing the cycling performance of the capacitor electrode prepared in Example B1 at a current density of 1 A / g. Detailed Implementation
[0033] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0034] The first aspect of this invention provides a nitrogen- and sulfur-doped carbon nanomaterial, wherein the carbon nanomaterial has a microporous structure and a mesoporous structure, and the BET specific surface area of the carbon nanomaterial is 800-2000 m². 2 / g, the proportion of the specific surface area within the micropores to the total specific surface area is 50-85%; the total pore volume of the nano-carbon material is greater than 1 cm³. 3 / g, the proportion of micropore volume to total pore volume is 30-50%; the mass percentage of carbon on the surface of the nano-carbon material, as determined by X-ray photoelectron spectroscopy, is 70-95%; the mass percentage of nitrogen is 3-20%; the mass percentage of sulfur is 0.1-10%; the mass percentage of carbon in the nano-carbon material, as determined by elemental analysis, is 30-60%; the mass percentage of nitrogen is 1-15%; the mass percentage of sulfur is 1-15%.
[0035] In some embodiments of the present invention, the nano-carbon material has a microporous structure and a mesoporous structure, and the BET specific surface area of the nano-carbon material is 800-2000 m². 2 / g, the proportion of the specific surface area within the micropores to the total specific surface area is 50-85%, preferably, the BET specific surface area of the nano-carbon material is 800-1600m². 2 / g, the specific surface area within the micropores accounts for 70-85% of the total specific surface area.
[0036] In some embodiments of the present invention, the total pore volume of the nanocarbon material is greater than 1 cm³. 3 / g, the micropore volume accounts for 30-50% of the total pore volume, preferably, the total pore volume of the nano-carbon material is greater than 1.45cm³. 3 / g, the proportion of micropore volume to total pore volume is 35-50%.
[0037] In some embodiments of the present invention, the mass percentage of carbon on the surface of the nano-carbon material, as measured by X-ray photoelectron spectroscopy, is 70-95%; the mass percentage of nitrogen is 3-20%; and the mass percentage of sulfur is 0.1-10%. Preferably, the mass percentage of carbon on the surface of the nano-carbon material, as measured by X-ray photoelectron spectroscopy, is 79-95%; the mass percentage of nitrogen is 5-11%; and the mass percentage of sulfur is 0.2-5%.
[0038] In some embodiments of the present invention, the mass percentage of carbon in the nano-carbon material, as measured by an elemental analyzer, is 30-60%; the mass percentage of nitrogen is 1-15%; and the mass percentage of sulfur is 1-15%. Preferably, the mass percentage of carbon in the nano-carbon material, as measured by an elemental analyzer, is 35-55%; the mass percentage of nitrogen is 5-15%; and the mass percentage of sulfur is 2-15%.
[0039] In this invention, the pore structure properties of the material are detected using the BET test method. Specifically, a Quantachrome AS-6B analyzer is used for measurement, and the specific surface area and pore volume of the material are obtained by the Brunauer-Emmett-Taller (BET) method.
[0040] In some embodiments of the present invention, preferably, the nitrogen- and sulfur-doped carbon nanomaterials may also contain oxygen, which may be present in various forms in the graphitized carbon layer formed during the preparation of the nitrogen- and sulfur-doped carbon nanomaterials. Preferably, the mass percentage of oxygen on the surface of the carbon nanomaterials, as measured by X-ray photoelectron spectroscopy, is 3-15%, more preferably 5-14%. Preferably, the mass percentage of oxygen in the carbon nanomaterials, as measured by elemental analysis, is 25-35%, more preferably 28-32%.
[0041] In this invention, the content of carbon, nitrogen, sulfur and oxygen elements on the surface of the nitrogen- and sulfur-doped nano-carbon material is determined by X-ray photoelectron spectroscopy; the content of carbon, nitrogen, sulfur and oxygen elements in the nitrogen- and sulfur-doped nano-carbon material is determined by elemental analysis.
[0042] In some embodiments of the present invention, preferably, the nano-carbon material has a mixed morphology of hollow cage-like and sheet-like structures, and the diameter of the hollow structure of the nano-carbon material is 5-50 nm. The morphology of the nano-carbon material can be determined by observation using high-resolution transmission electron microscopy, and the diameter of the hollow structure of the material is measured by transmission electron microscopy images.
[0043] In some embodiments of the present invention, preferably, the ratio of the intensity of the D peak to the intensity of the G peak in the Raman curve of the nano-carbon material (i.e., Ig) is... D / I G The ) is 0.5-1.5, preferably 0.5-1. The nano-carbon material of the present invention has obvious D peaks and G peaks, and has a certain degree of graphitization. Furthermore, using high-resolution transmission electron microscopy, it can be observed that the nano-carbon material of the present invention not only has a hollow structure but also a graphitized carbon layer. The graphitized carbon layer of the nano-carbon material can act as a buffer during lithium-ion intercalation, effectively improving the stability of the material.
[0044] In this invention, the term "nitrogen and sulfur doped nanocarbon materials" refers to nitrogen and sulfur elements. Specifically, this term refers to the nitrogen and sulfur elements present in various forms in the graphitized carbon layer formed during the preparation of nitrogen and sulfur doped nanocarbon materials.
[0045] In this invention, the term "graphitized carbon layer" refers to a carbon structure whose layered structure can be clearly observed under a high-resolution transmission electron microscope, rather than an amorphous structure.
[0046] In this invention, the term "mesopore" is defined as a pore with a diameter in the range of 2-50 nm. A pore with a diameter less than 2 nm is defined as a "micropore".
[0047] A second aspect of this invention provides a method for preparing nitrogen- and sulfur-doped carbon nanomaterials, the method comprising the following steps:
[0048] (1) Precursor preparation: A homogeneous solution is formed by mixing a nickel salt, a nitrogen-containing organic acid and a sulfur-containing potassium salt with a solvent, and then the solvent in the homogeneous solution is removed to obtain the precursor. The nitrogen-containing organic acid is ethylenediaminetetraacetic acid and / or 2,5-pyridinedicarboxylic acid, and the sulfur-containing potassium salt is potassium sulfate and / or potassium hydrogen sulfate.
[0049] (2) Calcination: Under an inert atmosphere, the precursor obtained in step (1) is calcined to obtain the pyrolysis product;
[0050] (3) Acid washing: Provide an aqueous solution containing the pyrolysis product obtained in step (2) and react it with acid, then separate the solid and liquid, wash and dry.
[0051] In some embodiments of the present invention, the method for preparing the nitrogen- and sulfur-doped carbon nanomaterials uses nitrogen-containing organic acids as carbon and nitrogen sources, sulfur-containing potassium salts as sulfur sources and activators, and nickel salts as catalysts and template agents. The prepared nitrogen- and sulfur-doped carbon nanomaterials have microporous and mesoporous structures, and the BET specific surface area of the carbon nanomaterials is 800-2000 m². 2 / g, the proportion of the specific surface area within the micropores to the total specific surface area is 50-85%; the total pore volume of the nano-carbon material is greater than 1 cm³. 3 / g, the micropore volume accounts for 30-50% of the total pore volume; the nano-carbon material has a large specific surface area, abundant pore structure, and a certain number of graphitized carbon layers.
[0052] In some embodiments of the present invention, the method for forming the homogeneous solution is not particularly limited. For example, it can be formed by heating, and more preferably by heating and stirring. The present invention also does not particularly limit the heating temperature and the stirring rate, as long as the method is sufficient to form the homogeneous solution.
[0053] In some embodiments of the present invention, preferably, in step (1), the precursor is obtained by dissolving a nickel salt, a nitrogen-containing organic acid, and a sulfur-containing potassium salt in a solvent to form a homogeneous solution, and then removing the solvent from the homogeneous solution. There is no particular limitation on the type of solvent, as long as it can form a homogeneous solution; for example, the solvent can be water, ethanol, etc., preferably water. There is also no particular limitation on the amount of solvent used, again as long as it can form a homogeneous solution. The solvent in the homogeneous solution can be removed by direct evaporation. The evaporation temperature and process can employ existing techniques known to those skilled in the art; for example, drying in an oven can remove the solvent from the homogeneous solution.
[0054] In some embodiments of the present invention, in step (1), the nickel salt can be a nickel-containing inorganic salt commonly used in the art. Preferably, the nickel salt can be selected from one or more of basic nickel carbonate, nickel acetate, nickel chloride, nickel nitrate and nickel sulfate, and is preferably basic nickel carbonate.
[0055] In some embodiments of the present invention, preferably, the nitrogen-containing organic acid is ethylenediaminetetraacetic acid and / or 2,5-pyridinedicarboxylic acid, more preferably ethylenediaminetetraacetic acid.
[0056] In some embodiments of the present invention, preferably, the sulfur-containing potassium salt can be potassium sulfate and / or potassium bisulfate, preferably potassium bisulfate.
[0057] In some embodiments of the present invention, preferably, the molar ratio of the nickel salt, the nitrogen-containing organic acid, and the sulfur-containing potassium salt, calculated based on nickel element, is 1:0.5-1:0.5-2, more preferably 1:0.7-1:0.5-1, and most preferably 1:1:1. This preferred embodiment is more advantageous for obtaining higher nitrogen and sulfur incorporation amounts and higher specific surface area.
[0058] In some embodiments of the present invention, preferably, in step (2), the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium, preferably a nitrogen atmosphere and / or an argon atmosphere.
[0059] In some embodiments of the present invention, the calcination method includes: heating to 400-1000°C at a heating rate of 2-10°C / min, preferably to 600-800°C at a heating rate of 5-10°C / min, calcining at a constant temperature for 1-8 hours, preferably 2-4 hours, and then cooling to room temperature at a cooling rate of 1-10°C / min, preferably 3-5°C / min.
[0060] In some embodiments of the present invention, preferably, in step (3), the pickling can be carried out using various inorganic acids and / or organic acids, as long as they can remove metallic elements such as nickel and potassium from the material. For example, the acid used for pickling can be selected from one or more of concentrated hydrochloric acid, concentrated sulfuric acid, and acetic acid, preferably concentrated hydrochloric acid. There are no special requirements on the amount of acid used, as long as it can remove metallic elements such as nickel and potassium from the material. In order to better remove metallic elements such as nickel and potassium from the material, preferably, an excess of acid is used during pickling.
[0061] In some embodiments of the present invention, preferably, the pickling temperature is 80-120°C, more preferably 90-100°C; and the contact reaction time is 6-24 hours, more preferably 8-12 hours.
[0062] In some embodiments of the present invention, the washing is used to remove acid residues on nitrogen- and sulfur-doped nano-carbon materials caused by the acid washing process. Therefore, various water washing methods that can wash nitrogen- and sulfur-doped nano-carbon materials to neutrality are applicable to the present invention.
[0063] In some embodiments of the present invention, drying is used to remove water from nitrogen- and sulfur-doped carbon nanomaterials. Drying can be performed under normal pressure or reduced pressure. Drying conditions may include a temperature of 100-120°C and a time of 6-10 hours.
[0064] In some embodiments of the present invention, preferably, the amounts of the nickel salt, nitrogen-containing organic acid, and sulfur-containing potassium salt are such that the mass percentage of carbon on the surface of the prepared nitrogen- and sulfur-doped carbon nanomaterial is 70-95%; the mass percentage of nitrogen is 3-20%; the mass percentage of sulfur is 0.1-10%; the mass percentage of carbon in the carbon nanomaterial is 30-60%; the mass percentage of nitrogen is 1-15%; and the mass percentage of sulfur is 1-15%.
[0065] In some embodiments of the present invention, preferably, the amounts of the nickel salt, nitrogen-containing organic acid, and sulfur-containing potassium salt are such that the mass percentage of carbon on the surface of the prepared nitrogen- and sulfur-doped carbon nanomaterial is 79-95%; the mass percentage of nitrogen is 5-11%; the mass percentage of sulfur is 0.2-5%; the mass percentage of carbon in the carbon nanomaterial is 35-55%; the mass percentage of nitrogen is 5-15%; and the mass percentage of sulfur is 2-15%.
[0066] A third aspect of the present invention provides a capacitor electrode material comprising an active substance, a conductive agent, and a binder, wherein the active substance is the nitrogen- or sulfur-doped nanocarbon material described in the first aspect or the nitrogen- or sulfur-doped nanocarbon material prepared according to the preparation method described in the second aspect.
[0067] In some embodiments of the present invention, the content and type of the conductive agent are well known to those skilled in the art, and the conductive agent may be selected from one or more of acetylene black, Ketjen black, graphene, and carbon nanotubes. The present invention preferably uses acetylene black as the conductive agent.
[0068] In some embodiments of the present invention, the adhesive is a binder, which can be any adhesive known in the art that can be used for capacitors. It can be selected from fluorinated resins and / or polyolefin compounds, such as one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose, polyvinyl alcohol, styrene-butadiene rubber latex, and acrylonitrile copolymer aqueous dispersions, preferably polytetrafluoroethylene (PTFE) and / or polyvinylidene fluoride (PVDF).
[0069] In some embodiments of the present invention, preferably, the mass ratio of nitrogen- and sulfur-doped nano-carbon materials, conductive agents and binders is 7-18:1-3:1, for example, it can be 9:0.5:0.5, 8:1:1, 8:1.5:0.5, 7:2:1 and any value within the range formed by any two of these values, preferably 8:1:1.
[0070] In some embodiments of the present invention, the current collector can be any type of current collector known to those skilled in the art, such as stainless steel mesh, aluminum foil, copper foil, etc. The present invention selects stainless steel mesh or copper foil as the current collector.
[0071] A fourth aspect of the present invention provides a capacitor electrode, the electrode comprising a current collector and an electrode material coated and / or filled on the current collector, wherein the electrode material is the electrode material described in the third aspect.
[0072] Since this invention only relates to the improvement of electrode active materials, there are no particular limitations on other components and structures of the capacitor when the nitrogen and sulfur doped nano-carbon materials are applied to the capacitor.
[0073] The fifth aspect of the present invention provides a method for preparing a capacitor electrode, the method comprising coating and / or filling a slurry containing an active material, a conductive agent, a binder, and a solvent onto a current collector, drying, and calendering or not calendering, wherein the active material is the nitrogen- or sulfur-doped nano-carbon material described in the first aspect or the nitrogen- or sulfur-doped nano-carbon material prepared according to the preparation method described in the second aspect.
[0074] According to a preferred embodiment of the present invention, the method for preparing the capacitor electrode includes:
[0075] Nitrogen and sulfur-doped nano-carbon materials, conductive agents, and binders are mixed, ground evenly, and then mixed with solvent to form a slurry. The slurry is then evenly coated onto the current collector, dried, and cut into electrode sheets.
[0076] According to another preferred embodiment of the present invention, the method for preparing the capacitor electrode includes:
[0077] Nitrogen and sulfur-doped nano-carbon materials, conductive agents, and binders are mixed, ground evenly, and then mixed with solvent to form a slurry. The slurry is ground until it reaches a clay-like state. The clay-like slurry is then stretched into a uniform thin sheet, dried, cut, and pressed onto a current collector to obtain an electrode sheet.
[0078] In some embodiments of the present invention, the solvent may be any solvent known in the art that can be used for the preparation of capacitor electrodes, such as ethanol and / or N-methylpyrrolidone, preferably N-methylpyrrolidone. The amount of solvent used is determined by the ability to form the desired coating slurry.
[0079] The sixth aspect of the present invention provides a capacitor comprising a battery casing, electrodes, a separator, and an electrolyte, wherein the electrodes comprise the capacitor electrodes described in the fourth aspect or capacitor electrodes prepared according to the preparation method described in the fifth aspect.
[0080] In some embodiments of the present invention, the electrolyte can be an electrolyte commonly used in the art for capacitors, such as an aqueous electrolyte and / or an organic electrolyte, with an aqueous electrolyte being particularly preferred.
[0081] In some embodiments of the present invention, preferably, the capacitor is a lithium-ion capacitor or a double-layer supercapacitor.
[0082] In some embodiments of the present invention, the lithium-ion capacitor uses a lithium metal sheet as the positive electrode and the electrolyte used is a lithium hexafluorophosphate electrolyte.
[0083] In some embodiments of the present invention, the separator used in the capacitor has electrical insulation and liquid retention properties, is disposed between the electrodes, and is sealed together with the electrodes within the battery casing. The separator can be any type of separator commonly used in the art, such as composite membranes made by welding or bonding together with wettable polyolefin microporous membranes of various grades of polyethylene, polypropylene, modified polyethylene felt, modified polypropylene felt, ultrafine glass fiber felt, vinylon felt, or nylon felt from known manufacturers. The present invention selects an aqueous separator and a cellulose separator as the separator for the dual supercapacitor, and a polypropylene separator as the separator for the lithium-ion capacitor.
[0084] The present invention will be described in detail below through embodiments.
[0085] The surface morphology of the material was characterized using high-resolution transmission electron microscopy (HRTEM). The HRTEM used was a JEM-2100 (Nippon Electron Ltd.), and the testing conditions were: accelerating voltage of 200 kV. The diameter of the hollow cage-like structure of the material was measured from the HRTEM images.
[0086] The pore structure properties of the material were detected using the BET test method. Specifically, a Quantachrome AS-6B analyzer was used for measurement. The specific surface area and pore volume of the material were obtained by the Brunauer-Emmett-Taller (BET) method. The mesopore distribution curve was calculated from the desorption curve using the Barrett-Joyner-Halenda (BJH) method, and the micropore size distribution curve was calculated from the isotherm using the Horvath-Kawazoe (HK) method.
[0087] The content of various elements and nitrogen, oxygen, and sulfur species on the material surface was determined by X-ray photoelectron spectroscopy (XPS). X-ray photoelectron spectroscopy analysis was performed on a Thermo Scientific ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software. The excitation source was monochromatic Al Kα X-rays with an energy of 1486.6 eV and a power of 150 W. The narrow scan passthrough energy was 30 eV, and the baseline vacuum during analysis was 6.53 × 10⁻⁶. - 9mbar, electron binding energy was corrected using the C1s peak (284.6 eV) of elemental carbon, and data processing was performed on Thermo Avantage software. Quantitative analysis was conducted using the sensitivity factor method in the analysis module. Before testing, the material was dried in a helium atmosphere at 150°C and 1 standard atmosphere for 3 hours.
[0088] The content of carbon, hydrogen, nitrogen, and sulfur in materials was determined using a combustion method with an Elementar Micro Cube elemental analyzer. Specifically, the material was burned at high temperature in the presence of oxygen, converting C, H, N, and S in the material into CO2, H2O, N2, and SO2, respectively. After removing interfering factors, the reaction gases were carried by a carrier gas into the chromatographic column for separation, and finally detected by a thermal conductivity cell. Oxygen analysis utilized high-temperature decomposition; in the presence of a carbon catalyst, oxygen in the sample was converted into CO, which was then detected using a TCD detector.
[0089] The Raman test uses visible laser Raman spectroscopy, which utilizes a 532 light source to Raman characterize the functional groups of the material and provide characteristic spectra.
[0090] Examples 1-3 illustrate nitrogen- and sulfur-doped carbon nanomaterials and their preparation methods.
[0091] Preparation Example 1
[0092] (1) Preparation of precursor: According to the molar ratio of nickel salt (calculated as nickel element), nitrogen-containing organic acid and sulfur-containing potassium salt of 1:1:1, 10g of basic nickel carbonate and 20.08g of ethylenediaminetetraacetic acid were weighed and dissolved in 150mL of deionized water and stirred evenly to obtain a solution. Then, 9.36g of potassium hydrogen sulfate was weighed and added to the solution. After heating and stirring at 95℃ for 4h, it was placed in an oven for drying to obtain 28g of precursor. The precursor was ground into powder and set aside for use.
[0093] (2) Calcination: Weigh 10g of precursor into a ceramic boat and place it in a tube furnace. Under nitrogen protection, heat the furnace to 650℃ at a heating rate of 5℃ / min and calcine at a constant temperature for 4h. Finally, cool the furnace to room temperature at a cooling rate of 5℃ / min to obtain 3.4g of pyrolysis product.
[0094] (3) Dissolve 3.4g of pyrolysis product in 50mL of deionized water, stir evenly, add 8mL of concentrated hydrochloric acid with a mass fraction of 37%, then heat to 105℃, stir for 12h, cool to room temperature, filter, wash with water until neutral, put the obtained product into an oven and dry overnight to obtain 600mg of nitrogen and sulfur doped nanocarbon material.
[0095] The transmission electron microscope image of the nitrogen- and sulfur-doped carbon nanomaterial is shown below. Figure 1 As shown, the high-resolution transmission electron microscope image is as follows: Figure 2As shown, from Figure 1 and Figure 2 It can be seen that the nano-carbon material has a mixed morphology of hollow cage-like and sheet-like structures, with the diameter of the hollow structure being 5-50 nm.
[0096] The N2 adsorption-desorption isotherm of the nitrogen- and sulfur-doped nanocarbon nanomaterial is as follows: Figure 3 As shown, the BET specific surface area of this carbon nanomaterial was calculated to be 1447.8 m² using isothermal adsorption-desorption curves. 2 / g, with a specific surface area of 1077.2m² within the micropores. 2 / g, accounting for 74.4% of the total specific surface area; the total pore volume of this nano-carbon material is 1.540 cm³. 3 / g, micropore volume is 0.595cm³ 3 / g, accounting for 38.6% of the total pore volume; the above data indicates that the nano-carbon material is mainly composed of microporous structure, while also containing a small amount of mesoporous structure.
[0097] Elemental analysis revealed that the nitrogen and sulfur-doped nanocarbon material contained 51.88% carbon, 2.95% sulfur, 8.28% nitrogen, 30.68% oxygen, and 6.21% hydrogen by mass.
[0098] The X-ray photoelectron spectroscopy (XPS) of the nitrogen- and sulfur-doped carbon nanomaterials is as follows: Figure 4 As shown in the figure, XPS peaks for C, N, O, and S are clearly visible. Characteristic peaks for sulfur are present at 163±1 eV and 167±1 eV, characteristic peaks for nitrogen are present at 398±1 eV and 400±1 eV, and characteristic peaks for oxygen are present at 530-533 eV, further confirming the effective doping of N and S elements, and the presence of oxygen. Based on the peak areas, the atomic percentages of each element on the surface of this nano-carbon material can be calculated: the mass percentage of carbon is 81.14%, the mass percentage of oxygen is 10.01%, the mass percentage of nitrogen is 8.51%, and the mass percentage of sulfur is 0.33%.
[0099] The S2p spectrum of the XPS of this carbon nanomaterial is as follows: Figure 5 As shown in the figure, sulfur mainly exists in the form of thiophene sulfur and sulfur oxides.
[0100] Raman test results of the nitrogen- and sulfur-doped nanocarbon nanomaterials are as follows: Figure 6 As shown in the figure, the nano-carbon material exhibits distinct D and G peaks, and I... D / I G =0.97, indicating that the nano-carbon material has a certain degree of graphitization.
[0101] Preparation Example 2
[0102] (1) Preparation of precursor: According to the molar ratio of nickel salt (calculated as nickel element), nitrogen-containing organic acid and sulfur-containing potassium salt of 1:1:0.5, 10g of basic nickel carbonate and 20.08g of ethylenediaminetetraacetic acid were weighed and dissolved in 200mL of deionized water and stirred evenly to obtain a solution. Then, 4.68g of potassium hydrogen sulfate was weighed and added to the solution. After heating and stirring at 95℃ for 4h, it was placed in an oven for drying to obtain 26g of precursor. The precursor was ground into powder and set aside for use.
[0103] (2) Calcination: Weigh 10g of precursor into a ceramic boat and place it in a tube furnace. Under nitrogen protection, heat the furnace to 650℃ at a heating rate of 5℃ / min and calcine at a constant temperature for 4h. Finally, cool the furnace to room temperature at a cooling rate of 5℃ / min to obtain 2.8g of pyrolysis product.
[0104] (3) Dissolve 2.8g of the pyrolysis product in 50mL of deionized water, stir evenly, add 6mL of concentrated hydrochloric acid, then heat to 105℃, stir for 24h, cool to room temperature, filter, wash with water until neutral, put the obtained product into an oven and dry overnight to obtain 400mg of nitrogen and sulfur doped nanocarbon material.
[0105] Transmission electron microscopy revealed that the nitrogen- and sulfur-doped carbon nanomaterials exhibited a mixed morphology of hollow cage-like and sheet-like structures, with the diameter of the hollow structures ranging from 5 to 50 nm.
[0106] The BET specific surface area of this nitrogen- and sulfur-doped carbon nanomaterial was determined to be 845.86 m² using isothermal adsorption-desorption curves, as measured by the BET test method. 2 / g, the specific surface area within the micropores is 707.04m². 2 / g, accounting for 83.6% of the total specific surface area; the total pore volume of this nano-carbon material is 1.51cm³. 3 / g, micropore volume is 0.59cm³ 3 / g, accounting for 39% of the total pore volume; the above data indicates that the nano-carbon material is mainly composed of microporous structure, while also containing a small amount of mesoporous structure.
[0107] Elemental analysis revealed that the nitrogen and sulfur-doped nanocarbon material contained 52.02% carbon, 2.52% sulfur, 9.58% nitrogen, 29.08% oxygen, and 6.80% hydrogen by mass.
[0108] X-ray photoelectron spectroscopy revealed that the surface of this nitrogen and sulfur-doped carbon nanomaterial contained 79.4% carbon, 8.8% oxygen, 10.77% nitrogen, and 1.03% sulfur by mass.
[0109] Raman spectroscopy revealed that the nitrogen- and sulfur-doped carbon nanomaterial exhibited distinct D and G peaks, I D / I G =0.995, indicating that the nano-carbon material has a certain degree of graphitization.
[0110] Preparation Example 3
[0111] (1) Preparation of precursor: According to the molar ratio of nickel salt (calculated as nickel element), nitrogen-containing organic acid and sulfur-containing potassium salt of 1:0.7:1, 10g of basic nickel carbonate and 14.05g of ethylenediaminetetraacetic acid were weighed and dissolved in 200mL of deionized water and stirred evenly to obtain a solution. Then, 9.36g of potassium hydrogen sulfate was weighed and added to the solution. After heating and stirring at 95℃ for 4h, it was placed in an oven for drying to obtain 27g of precursor. The precursor was ground into powder and set aside for use.
[0112] (2) Calcination: Weigh 10g of precursor into a ceramic boat and place it in a tube furnace. Under nitrogen protection, heat the furnace to 650℃ at a heating rate of 5℃ / min and calcine at a constant temperature for 4h. Finally, cool the furnace to room temperature at a cooling rate of 5℃ / min to obtain 4.3g of pyrolysis product.
[0113] (3) Dissolve 4.3g of pyrolysis product in 50mL of deionized water, stir evenly, add 8mL of concentrated hydrochloric acid, then heat to 105℃, stir for 24h, cool to room temperature, filter, wash with water until neutral, put the obtained product into an oven and dry overnight to obtain 332mg of nitrogen and sulfur doped nanocarbon material.
[0114] Transmission electron microscopy revealed that the nitrogen- and sulfur-doped carbon nanomaterials exhibited a mixed morphology of hollow cage-like and sheet-like structures, with the diameter of the hollow cage-like structures ranging from 5 to 50 nm.
[0115] The BET specific surface area of this nitrogen- and sulfur-doped carbon nanomaterial was determined to be 1356.5 m² using isothermal adsorption-desorption curves, as measured by the BET test method. 2 / g, with a specific surface area of 960.3m² within the micropores. 2 / g, accounting for 71% of the total specific surface area; the total pore volume of this nano-carbon material is 1.49 cm³. 3 / g, micropore volume is 0.58cm³ 3 / g, accounting for 38.9% of the total pore volume; the above data indicates that the nano-carbon material is mainly composed of microporous structure, while also containing a small amount of mesoporous structure.
[0116] Elemental analysis revealed that the nitrogen and sulfur-doped nanocarbon material contained 45.43% carbon, 12.05% sulfur, 5.79% nitrogen, 29.54% oxygen, and 7.19% hydrogen by mass.
[0117] X-ray photoelectron spectroscopy revealed that the surface of this nitrogen- and sulfur-doped carbon nanomaterial contained 79.3% carbon, 13.42% oxygen, 5.24% nitrogen, and 2.04% sulfur by mass.
[0118] Raman spectroscopy revealed that the nitrogen- and sulfur-doped carbon nanomaterial exhibited distinct D and G peaks, I D / I G =0.99, indicating that the nano-carbon material has a certain degree of graphitization.
[0119] Comparative Preparation Example 1
[0120] Nitrogen-doped carbon nanomaterials were prepared according to the method of Preparation Example 1, except that potassium bisulfate was not used in the precursor preparation process of step (1).
[0121] (1) Material preparation: Accurately weigh 10g of basic nickel carbonate and 20.08g of ethylenediaminetetraacetic acid, dissolve them in 100mL of deionized water, and stir until homogeneous. After heating and stirring at 95℃ for 4h, place it in an oven. Finally, 25g of precursor was obtained, which was ground into powder and set aside for use.
[0122] (2) Calcination: Accurately weigh 10g of precursor into a ceramic boat, then place it in a tube furnace. Under nitrogen protection, heat the furnace to 600℃ at a heating rate of 5℃ / min, calcine at a constant temperature for 4h, and finally cool it to room temperature at a rate of 5℃ / min to obtain 3.0g of blackish-gray pyrolysis product.
[0123] (3) Dissolve the pyrolysis product in an appropriate amount of deionized water, stir well, and then add 10 mL of 37% concentrated hydrochloric acid. The temperature is then raised to 100°C and stirred for 12 h. After cooling to room temperature, filter, wash with water until neutral, and then place in an oven to dry overnight. 800 mg of nitrogen-doped carbon nanomaterials are obtained.
[0124] The BET specific surface area of this nitrogen-doped carbon nanomaterial was determined to be 328.5 m² using the BET test method and calculated from the isothermal adsorption-desorption curve. 2 / g, with a specific surface area of 30.7m² within the micropores. 2 / g, accounting for 10% of the total specific surface area; the total pore volume of this nano-carbon material is 1.45cm³. 3 / g, micropore volume is 0.05cm³3 / g, accounting for 3.4% of the total pore volume; the above data indicates that the nitrogen-doped carbon nanomaterial is mainly mesoporous;
[0125] Elemental analysis revealed that the nitrogen-doped carbon nanomaterial contained 55.43% carbon, 12.5% nitrogen, 25.38% oxygen, and 6.69% hydrogen by mass.
[0126] X-ray photoelectron spectroscopy revealed that the surface of this nitrogen-doped carbon nanomaterial contained 84.91% carbon, 9.53% oxygen, and 5.56% nitrogen by mass.
[0127] Raman spectroscopy revealed that this nitrogen-doped carbon nanomaterial exhibited distinct D and G peaks, I D / I G =0.85, indicating that the nano-carbon material has a certain degree of graphitization.
[0128] Comparative Preparation Example 2
[0129] The nano-carbon material was prepared according to the method of Preparation Example 1, except that ethylenediaminetetraacetic acid and potassium hydrogen sulfate were not used in the precursor preparation process of step (1).
[0130] (1) Material preparation: 10g of basic nickel carbonate and 20g of citric acid were dissolved in 100mL of deionized water, heated and stirred at 95℃ for 4h, and then placed in an oven to dry. The precursor obtained after drying was ground into powder and set aside for use.
[0131] (2) Calcination: Weigh 10g of the precursor and place it in a tube furnace. Under nitrogen protection, heat the precursor to 650℃ at a heating rate of 5℃ / min, calcine at a constant temperature for 2 hours, and finally cool it naturally to room temperature to obtain a black primary product.
[0132] (3) The initial product was then dissolved in an appropriate amount of deionized water, stirred evenly, and 10 mL of 37% concentrated hydrochloric acid was added. The temperature was then raised to 95°C and stirred for 12 h. After cooling to room temperature, the mixture was filtered and washed with water until neutral. It was then placed in an oven and dried overnight to obtain 2 g of doped carbon nanomaterials.
[0133] The BET specific surface area of this carbon nanomaterial was determined to be 285.3 m² using the BET test method and calculated from the isothermal adsorption-desorption curve. 2 / g, with a specific surface area of 10.28m² within the micropores. 2 / g, accounting for 3.6% of the total specific surface area; the total pore volume of this nano-carbon material is 1.53cm³. 3 / g, micropore volume is 0.02cm³ 3 / g, accounting for 1.3% of the total pore volume; the above data indicates that the nano-carbon material is mainly composed of mesoporous structure;
[0134] Elemental analysis revealed that the carbon nanomaterial contained 60.25% carbon by mass, 25.06% oxygen by mass, and 5.68% hydrogen by mass.
[0135] X-ray photoelectron spectroscopy revealed that the carbon content on the surface of this nanomaterial was 85.61% by mass, the oxygen content was 8.72% by mass, and the nickel content was 5.67% by mass.
[0136] Raman spectroscopy revealed that the nano-carbon material exhibited distinct D and G peaks, I... D / I G =0.79, indicating that the nano-carbon material has a certain degree of graphitization.
[0137] Cyclic voltammetry tests were performed on the nitrogen and sulfur-doped carbon nanomaterials prepared in Examples 1-3. This invention exemplarily provides cyclic voltammetry curves of the nitrogen and sulfur-doped carbon nanomaterials prepared in Example 1 at different scan rates, as shown below. Figure 7 As shown in the figure, the curve is elliptical and has redox peaks, indicating that the doping of nitrogen and sulfur atoms introduces pseudocapacitance, thereby improving the overall performance of the material.
[0138] Examples A1-A3 illustrate capacitor electrode materials, capacitor electrodes, and their preparation methods.
[0139] Example A1
[0140] Preparation of capacitor electrodes: 32 mg of nitrogen- and sulfur-doped nano-carbon material prepared in Example 1 was weighed. The nano-carbon material, conductive agent (acetylene black), and binder (polytetrafluoroethylene) were mixed in a mass ratio of 8:1:1. An appropriate amount of anhydrous ethanol was added, and the mixture was thoroughly ground. The slurry was rolled into a thin sheet and then dried overnight in a vacuum oven at 80°C. After drying, it was cut into electrode sheets with a diameter of 10 mm. Subsequently, the electrode sheets were pressed into a stainless steel mesh current collector using a hydraulic press. The active material content on the electrode sheet was 0.8-3 mg.
[0141] Example A2
[0142] Preparation of capacitor electrode: The capacitor electrode was prepared according to the method of Example A1, except that the same weight of nitrogen and sulfur doped nano-carbon material obtained in Preparation Example 2 was weighed as the electrode active material.
[0143] Example A3
[0144] Preparation of capacitor electrode: The capacitor electrode was prepared according to the method of Example A1, except that the same weight of nitrogen and sulfur doped nano-carbon material obtained in Preparation Example 3 was weighed as the electrode active material.
[0145] Comparative Example A1
[0146] Preparation of capacitor electrode: The capacitor electrode was prepared according to the method of Example A1, except that the same weight of nitrogen-doped carbon nanomaterial prepared in Comparative Preparation Example 1 was weighed as the electrode active material.
[0147] Comparative Example A2
[0148] Preparation of capacitor electrode: The capacitor electrode was prepared according to the method of Example A1, except that the same weight of the undoped nano-carbon material prepared in Comparative Preparation Example 2 was weighed as the electrode active material.
[0149] Test Example A is used to test the capacitance performance of capacitor electrodes.
[0150] Test Case A
[0151] The capacitance performance was tested using a three-electrode system: the electrodes prepared in Examples A1-A3 and Comparative Examples A1-A2 were used as working electrodes, a platinum electrode as counter electrode, a mercuric oxide electrode as reference electrode, and a 6 mol / L KOH aqueous solution as electrolyte.
[0152] The assembled three-electrode system was subjected to constant current charge-discharge tests. The test voltage range (relative to the mercury oxide electrode) was 0V to -1V, and the specific capacitance was recorded at different current densities (0.5-20A / g).
[0153] The capacitor electrode prepared in Example A1 has a specific capacitance of 358 F / g at a current density of 0.5 A / g, 280 F / g at a current density of 1 A / g, 210 F / g at a current density of 5 A / g, 176 F / g at a current density of 10 A / g, and 148 F / g at a current density of 20 A / g.
[0154] The capacitor electrode prepared in Example A2 has a specific capacitance of 270 F / g at a current density of 1 A / g.
[0155] The capacitor electrode prepared in Example A3 has a specific capacitance of 190 F / g at a current density of 1 A / g.
[0156] The capacitor electrode prepared in Comparative Example A1 has a specific capacitance of 150 F / g at a current density of 1 A / g.
[0157] The capacitor electrode prepared in Comparative Example A2 has a specific capacitance of 120 F / g at a current density of 1 A / g.
[0158] Examples B1-B3 illustrate capacitor electrode materials, capacitor electrodes, and their preparation methods.
[0159] Example B1
[0160] Preparation of capacitor electrodes: Weigh 80 mg of nitrogen- and sulfur-doped nano-carbon material prepared in Example 1. Mix the nano-carbon material, conductive agent (acetylene black), and binder (polyvinylidene fluoride) in a mass ratio of 8:1:1. Add an appropriate amount of solvent (N-methylpyrrolidone) and grind thoroughly. Coat the slurry onto a clean copper foil and dry it overnight in a vacuum oven at 80°C. After drying, cut it into circular electrodes with a diameter of 10 mm and a mass of 2.5 mg. The active material content on the electrodes is 0.8-2 mg.
[0161] Example B2
[0162] Preparation of capacitor electrode: Weigh 32 mg of nitrogen- and sulfur-doped nano-carbon material prepared in Example 1. Mix the nano-carbon material, conductive agent (acetylene black), and binder (polytetrafluoroethylene) in a mass ratio of 8:1:1. Add an appropriate amount of solvent (anhydrous ethanol) and grind thoroughly until the slurry resembles clay. Use a glass rod to stretch and roll the clay-like slurry into a uniform thin sheet, and then place it in an oven to dry at 80°C for 2-3 hours. After complete drying, cut it into circular electrode sheets with a diameter of 10 mm and a mass of 2.1 mg. Then, use a hydraulic press to press the circular electrode sheets onto a stainless steel mesh current collector under a pressure of 10 MPa to obtain the capacitor electrode.
[0163] Example B3
[0164] Preparation of capacitor electrode: The capacitor electrode was prepared according to the method of Example B2, except that nitrogen and sulfur doped nano-carbon material, conductive agent (acetylene black) and binder (polytetrafluoroethylene) were mixed in a mass ratio of 7:2:1.
[0165] Comparative Example B1
[0166] Preparation of capacitor electrode: The capacitor electrode was prepared according to the method of Example B2, except that the same weight of nitrogen-doped carbon nanomaterial prepared in Comparative Preparation Example 1 was weighed as the electrode active material.
[0167] Comparative Example B2
[0168] Preparation of capacitor electrode: The capacitor electrode was prepared according to the method of Example B2, except that the same weight of the nano-carbon material prepared in Comparative Preparation Example 2 was weighed as the electrode active material.
[0169] Comparative Example B3
[0170] Preparation of capacitor electrodes: Capacitor electrodes were prepared according to the method of Example B2, except that the same weight of commercially available graphite (purchased from BTR Corporation) was weighed as the electrode active material.
[0171] Test Example B is used to illustrate lithium-ion capacitors and their preparation methods.
[0172] Test Case B
[0173] Capacitor assembly: The capacitor electrodes and polypropylene separators prepared in Examples B1-B3 and Comparative Examples B1-B3 were immersed in lithium hexafluorophosphate electrolyte for 0.5 h and then removed. Using lithium hexafluorophosphate as electrolyte, they were assembled into button-type lithium-ion capacitors in the order of battery case (positive electrode) - lithium sheet - separator - electrode - battery case (negative electrode).
[0174] Performance testing: The specific capacitance, rate capability, and cycle stability of the fabricated button-type lithium-ion capacitors were characterized using a Blue Electric system. Within a voltage range of 0-3V, the capacitors were first discharged and then charged at different current densities (0.1-2A / g).
[0175] The present invention provides, by way of example, the constant current charge-discharge curves of the nitrogen- and sulfur-doped carbon nanomaterials prepared in Example 1, as follows: Figure 8 As shown, from Figure 8 The constant current charge-discharge curves show that the curves exhibit an asymmetric shape. The other preparation examples are similar, indicating that the nitrogen and sulfur doped carbon nanomaterials provided by this invention have double-layer capacitance and pseudocapacitance, and can be applied to lithium-ion capacitors or double-layer supercapacitors.
[0176] The capacitor electrode prepared in Example B1 exhibits an initial discharge specific capacity of 1540 mAh / g and a charge specific capacity of 900 mAh / g at a current density of 0.1 A / g. Its specific capacity at different current densities is shown below. Figure 9 As shown. At a current density of 0.1 A / g, the stabilized specific capacity exceeds 800 mAh / g. At a current density of 1 A / g, the specific capacity is 395 mAh / g. Even when the current density is increased to 2 A / g, the specific capacity still reaches 290 mAh / g. Furthermore, as... Figure 12 As shown, the first capacitor prepared in Example B1 retains 80% of its capacitance after 1000 cycles at a current density of 1 A / g.
[0177] The capacitor electrode prepared in Example B2 exhibits an initial discharge specific capacity of 1557.3 mAh / g and a charge specific capacity of 950.7 mAh / g at a current density of 0.1 A / g. Its specific capacity at different current densities is shown below. Figure 10As shown, at a current density of 0.1 A / g, the stabilized specific capacity exceeds 900 mAh / g. At a current density of 1 A / g, the specific capacity is 420 mAh / g. When the current density is increased to 2 A / g, the specific capacity still reaches 300 mAh / g. Furthermore, at a current density of 1 A / g, after 1000 cycles, the capacitance retention of the capacitor electrode prepared in Example B2 is close to 60%.
[0178] The capacitor electrode prepared in Example B3 exhibits an initial discharge specific capacity of 1485.2 mAh / g and a charge specific capacity of 850.1 mAh / g at a current density of 0.1 A / g. Its specific capacity at different current densities is shown below. Figure 11 As shown, at a current density of 0.1 A / g, the stabilized specific capacity exceeds 800 mAh / g. At a current density of 1 A / g, the specific capacity is 300 mAh / g. When the current density is increased to 2 A / g, the specific capacity still reaches 190 mAh / g. After 1000 cycles at a current density of 1 A / g, the capacity retention is 71%.
[0179] The capacitor electrode prepared in Comparative Example B1 exhibited a stable specific capacity of 600 mAh / g at a current density of 0.1 A / g. At a current density of 1 A / g, the specific capacity was 260 mAh / g. When the current density was increased to 2 A / g, the specific capacity dropped to only 180 mAh / g. After 1000 cycles at a current density of 1 A / g, the capacity retention was 50%.
[0180] The capacitor electrode prepared in Comparative Example B2 exhibits a stable specific capacity of 500 mAh / g at a current density of 0.1 A / g. At a current density of 1 A / g, the specific capacity is 180 mAh / g. When the current density is increased to 2 A / g, the specific capacity drops to only 130 mAh / g. After 1000 cycles at a current density of 1 A / g, the capacity retention is close to 60%.
[0181] The capacitor electrode prepared in Comparative Example B3 exhibited a maximum specific capacity of only 360 mAh / g after stabilization at a current density of 0.1 A / g. Furthermore, after 1000 cycles at a current density of 1 A / g, the capacity retention was less than 50%.
[0182] The data analysis above shows that when the nitrogen and sulfur-doped nano-carbon materials of the present invention are applied to lithium-ion capacitors, they exhibit excellent specific capacitance, rate performance and cycle performance; when applied to double-layer supercapacitors, at a current density of 0.5 A / g in an aqueous electrolyte, the single-electrode specific capacitance can reach up to 358 F / g, exhibiting excellent capacitance performance.
[0183] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A nitrogen- and sulfur-doped nanocarbon material, characterized in that, The nano-carbon material possesses both microporous and mesoporous structures, and its BET specific surface area is 800-2000 m². 2 / g, the proportion of microporous specific surface area to total specific surface area is 50-85%; the total pore volume of the nano-carbon material is greater than 1cm³. 3 / g, the proportion of micropore volume to total pore volume is 30-50%; the mass percentage of carbon on the surface of the nano-carbon material, as determined by X-ray photoelectron spectroscopy, is 70-95%; the mass percentage of nitrogen is 5-11%; the mass percentage of sulfur is 0.1-10%; the mass percentage of carbon in the nano-carbon material, as determined by elemental analysis, is 30-60%; the mass percentage of nitrogen is 1-15%; the mass percentage of sulfur is 1-15%; the nano-carbon material has a mixed morphology of hollow cage-like and sheet-like structures.
2. The nanocarbon material according to claim 1, wherein, The BET specific surface area of the nano-carbon material is 800-1600 m². 2 / g, the proportion of the specific surface area within the micropores to the total specific surface area is 70-85%; the total pore volume of the nano-carbon material is greater than 1.45 cm³. 3 / g, the proportion of micropore volume to total pore volume is 35-50%; the mass percentage of carbon on the surface of the nano-carbon material, as determined by X-ray photoelectron spectroscopy, is 79-95%; the mass percentage of sulfur is 0.2-5%; the mass percentage of carbon in the nano-carbon material, as determined by elemental analysis, is 35-55%; the mass percentage of nitrogen is 5-15%; and the mass percentage of sulfur is 2-15%.
3. The nanocarbon material according to claim 1 or 2, wherein, The diameter of the hollow structure of the nano-carbon material is 5-50 nm.
4. The nanocarbon material according to claim 1 or 2, wherein, In the Raman curve of the nano-carbon material, the intensity ratio of the D peak to the G peak is 0.5-1.
5.
5. The nanocarbon material according to claim 4, wherein, In the Raman curve of the aforementioned carbon nanomaterial, the intensity ratio of the D peak to the G peak is 0.5-1.
6. A method for preparing nitrogen- and sulfur-doped nanocarbon materials according to any one of claims 1-5, characterized in that, The preparation method includes the following steps: (1) Preparation of precursor: A homogeneous solution is formed by mixing nickel salt, nitrogen-containing organic acid and sulfur-containing potassium salt with a solvent, and then the solvent in the homogeneous solution is removed to obtain the precursor. The nitrogen-containing organic acid is ethylenediaminetetraacetic acid and / or 2,5-pyridinedicarboxylic acid, and the sulfur-containing potassium salt is potassium sulfate and / or potassium hydrogen sulfate. In step (1), the molar ratio of nickel salt, nitrogen-containing organic acid and sulfur-containing potassium salt based on nickel element is 1:0.5-1:0.5-2. (2) Calcination: Under an inert atmosphere, the precursor obtained in step (1) is calcined to obtain the pyrolysis product; (3) Acid washing: Provide an aqueous solution containing the pyrolysis product obtained in step (2) and react it with acid, then separate the solid and liquid, wash and dry.
7. The preparation method according to claim 6, wherein, In step (1), the nickel salt is selected from one or more of basic nickel carbonate, nickel acetate, nickel chloride, nickel nitrate and nickel sulfate; The nitrogen-containing organic acid is ethylenediaminetetraacetic acid; the sulfur-containing potassium salt is potassium hydrogen sulfate.
8. The preparation method according to claim 7, wherein, In step (1), the nickel salt is basic nickel carbonate.
9. The preparation method according to claim 6, wherein, In step (2), the calcination method includes: heating to 400-1000℃ at a heating rate of 2-10℃ / min, calcining at a constant temperature for 1-8h, and then cooling to room temperature at a cooling rate of 1-10℃ / min; the inert atmosphere is a nitrogen atmosphere and / or an argon atmosphere.
10. The preparation method according to claim 9, wherein, In step (2), the calcination method includes: heating to 600-800℃ at a heating rate of 5-10℃ / min, calcining at a constant temperature for 2-4 hours, and then cooling to room temperature at a cooling rate of 3-5℃ / min.
11. The preparation method according to claim 6, wherein, In step (3), the acid used for pickling is selected from one or more of concentrated hydrochloric acid, concentrated sulfuric acid and acetic acid.
12. The preparation method according to claim 11, wherein, In step (3), the acid used for pickling is concentrated hydrochloric acid.
13. The preparation method according to claim 6 or 11, wherein, In step (3), the pickling temperature is 80-120℃; the contact reaction time is 6-24h.
14. The preparation method according to claim 13, wherein, In step (3), the pickling temperature is 90-100℃; the contact reaction time is 8-12h.
15. A capacitor electrode material, the electrode material comprising an active substance, a conductive agent, and a binder, characterized in that, The active material is the nitrogen- or sulfur-doped nanocarbon material according to any one of claims 1-5, or the nitrogen- or sulfur-doped nanocarbon material prepared according to any one of claims 6-14.
16. The electrode material according to claim 15, wherein, The mass ratio of nitrogen- and sulfur-doped nano-carbon materials, conductive agents, and binders is 7-18:1-3:
1.
17. A capacitor electrode, comprising a current collector and an electrode material coated and / or filled on the current collector, characterized in that, The electrode material is the electrode material described in claim 15 or 16.
18. A method for preparing a capacitor electrode, the method comprising coating and / or filling a slurry containing an active material, a conductive agent, a binder, and a solvent onto a current collector, drying, and calendering or not calendering, characterized in that, The active material is the nitrogen- or sulfur-doped nanocarbon material according to any one of claims 1-5, or the nitrogen- or sulfur-doped nanocarbon material prepared according to any one of claims 6-14.
19. The method for preparing capacitor electrodes according to claim 18, wherein, The solvent is ethanol and / or N-methylpyrrolidone.
20. The method for preparing capacitor electrodes according to claim 19, wherein, The solvent is N-methylpyrrolidone.
21. A capacitor comprising a battery casing, electrodes, a separator, and an electrolyte, characterized in that, The electrode includes the capacitor electrode of claim 17 or the capacitor electrode prepared by the preparation method according to any one of claims 18-20.
22. The capacitor according to claim 21, wherein, The capacitor is a lithium-ion capacitor or a double-layer supercapacitor.
Citation Information
Patent Citations
Nitrogen-sulfur double-doped mesoporous carbon electrode material as well as preparation method and application thereof
CN104445144A
Carbon nano cage carrier-based metal monoatomic catalyst and preparation method thereof
CN109126857A
Carbon coated transition metal nano-composite material and preparation method and application thereof
CN109304201A